PENGARUH KOMUNIKASI, KERJASAMA TIM DAN REWARD TERHADAP KINERJA GURU PADA SMK SARASWATI 2 DENPASAR - Ni Kadek Eli Meliantari; I Wayan Sujana; Ni Nyoman Ari Novarini (EMAS, 2022)
Maintaining and improving teacher performance today is very important for all schools in order to increase the number of students for the sustainability of the school, because currently there are so many new Public Vocational High Schools and Private Vocational High Schools that have been established resulting in increasingly fierce competition to get students. Therefore, the role of teachers today is very important in improving the existence of schools. The population and sample in this study amounted to 35 people, namely all teachers who are actively teaching at SMK Saraswati 2 Denpasar, to find out respondents' responses to each variable, the saturated sample method was used. The type of data in this study is quantitative data. Data collection methods are interviews, observations and questionnaires. Data analysis techniques include validity and reliability testing, classical assumption test, normality test, multicollinearity test, heteroscedasticity test, multiple linear regression analysis, multiple correlation analysis, coefficient of determination (R2), t test and F test. The results showed that communication, teamwork and rewards has a positive and significant effect on teacher performance, so the school leader or principal should always communicate well with teachers, provide direction and guidance regarding teamwork and pay attention to appropriate rewards for teachers to improve teacher performance at SMK Saraswati 2 Denpasar.